2006
DOI: 10.1097/01.mao.0000231599.33585.c6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Vestibular-Evoked Myogenic Potential Induced by Bone-Conducted Stimuli

Abstract: The results of B-VEMP were almost the same as those for A-VEMP, at least, for patients without conductive hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…As previously mentioned, there has been relatively little data directly comparing the cVEMP in response to AC versus BC stimuli within the same study. Miyamoto et al (2006) evaluated the interaural amplitude ratios to both AC and BC stimuli and found them to be highly correlated (Miyamoto et al 2006), whereas Sheykholeslami et al (2000) reported that cVEMPs evoked by BC tonebursts were shorter in latency than those evoked by AC tonebursts (Sheykholeslami et al 2000). Welgampola et al (2003) reported lower cVEMP thresholds in response to BC as compared with AC stimuli (Welgampola et al 2003).…”
Section: Ac Versus Bc Stimulimentioning
confidence: 96%
“…As previously mentioned, there has been relatively little data directly comparing the cVEMP in response to AC versus BC stimuli within the same study. Miyamoto et al (2006) evaluated the interaural amplitude ratios to both AC and BC stimuli and found them to be highly correlated (Miyamoto et al 2006), whereas Sheykholeslami et al (2000) reported that cVEMPs evoked by BC tonebursts were shorter in latency than those evoked by AC tonebursts (Sheykholeslami et al 2000). Welgampola et al (2003) reported lower cVEMP thresholds in response to BC as compared with AC stimuli (Welgampola et al 2003).…”
Section: Ac Versus Bc Stimulimentioning
confidence: 96%
“…A large amount of data has been obtained by changing several parameters, such as electrode positioning, patient position (e.g., supine, sitting), stimulus type (e.g., tone burst, click), and stimulus application (air or bone conduction) [1][2][3][4][5] . Current literature reports a VEMP response rate of 80-100% [2,3] .…”
Section: Discussionmentioning
confidence: 99%
“…Many authors consequently normalize the VEMP amplitude by dividing it by a measure of the muscle tone (e.g. Karino et al, 2005;Welgampola and Colebatch, 2005;Miyamoto et al, 2006;Brantberg et al, 2007;Sandhu and Bell, 2008;Seo et al, 2008;Brantberg and Verrecchia, 2009 providing an unequivocal signature of the inhibition arising from the vestibular end organs.…”
Section: Introductionmentioning
confidence: 99%